Tezos : governance in the cryptocurrency world - Barua, S. K. (Samir K.); Varma, J. R. (Jayanth R.) (London : Indian Institute of Management, Ahmedabad, 2020)
The case deals with a governance crisis confronting Arthur and Kathleen Breitman, the founders of Tezos. All developmental activities in Tezos were stalled after the Breitmans lost access to the funds raised through an initial coin offering (ICO) held four months earlier. Moreover, a series of class-action lawsuits in the United States alleged that the USD 230 million ICO was an illegal security offering and demanded compensatory damages besides a refund of the investment. The governance problems arose from a situation in which a not-for-profit entity, Tezos Foundation (TF), and a for-profit entity, Dynamic Ledger Solutions (DLS), were inextricably linked with each other. While TF was registered in Switzerland as a trust, DLS was registered in the US as a company. Although DLS would be the operating entity charged with the responsibility of developing the Tezos network, it had to depend on TF for funds to complete the work before the launch of the network.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Cryptocurrencies -- Law and legislation -- Case studies